Assessing User Satisfaction in Hadirku Through an Extended TAM Framework - Jaya, Aswadi; Zainarthur, Henry; Sijabat, Apriani; Dina, Aulia Rahma; Faturahman, Adam (International Transactions on Artificial Intelligence, 2025)
The rapid advancement of Information and Communication Technology (ICT) has accelerated the transition from manual, paper based attendance systems toward digital platforms that promote efficiency and environmental sustainability through reduced paper usage. In this context, the Hadirku online attendance platform has been increasingly adopted across educational, organizational, and eventmanagement settings. This study employs the Technology Acceptance Model (TAM), extended with Service Quality, Organizational Support, and Information Security, to examine determinants of User Satisfaction and Continued Usage. A quantitative design was implemented with 200 valid respondents, and SmartPLS was used to assess construct validity and structural relationships. Reliability was strong (Cronbach’s α = 0.77–0.92), and model fit met recommended thresholds (SRMR = 0.057; NFI = 0.91). The study aims to analyze how perceived usefulness, ease of use, service quality, information security, and organizational support influence user engagement with Hadirku. Findings reveal that information security and perceived usefulness significantly predict continued usage intention, while perceived ease of use and organizational support enhance user satisfaction. Users overall reported positive experiences and strong behavioral intention to continue using the platform. This study contributes to digital transformation and Green ICT literature by providing an extended TAM framework that explains sustained engagement with online attendance systems. The results offer practical insights for platform developers and institutions seeking to optimize user trust, system reliability, and sustainable administrative practices.